Exploring the Integration of Artificial Intelligence and IoT in Smart Farming: A Systematic Review: Menjelajahi Integrasi Kecerdasan Buatan dengan IoT dalam Pertanian Cerdas: Tinjauan Sistematis - Aswin Rosadi; Mokh Sholihul Hadi (JOINCS (Journal of Informatics, Network, and Computer Science), 2025)
Abstract – This study examines the integrationof artificial intelligence (AI) and the Internet ofThings (IoT) in smart farming through asystematic literature review. This researchfocuses on the application of AI, the AIoTarchitecture, the datasets used, and theproblems solved by this technology. The mainproblems faced are the complexity oftechnology integration and the limitations ofinfrastructure in implementation in the field.The purpose of the research is to provide acomprehensive understanding of theadvancements and challenges of AIoTtechnology in the agricultural sector. Themethod used follows the guidance ofKitchenham (2007) by reviewing the latestrelevant literature. The results show that AIoThas great potential in improving the efficiencyand sustainability of the agricultural sectorthrough efficient data management and datadrivendecision-making. However, the successof the implementation of this technology ishighly dependent on the availability of qualitydatasets and the adaptability of the technologyat scale. This research provides practicalrecommendations for the development andapplication of AIoT in various smartagriculture scenarios in the future.